Spatial patterns of Anchoveta (Engraulis ringens) eggs and larvae in relation to pCO2 in the Peruvian upwelling system. Issue 1855 (24th May 2017) - Shen, Sara G.; Thompson, Andrew R.; Correa, Jonathan; Fietzek, Peer; Ayón, Patricia; Checkley, David M.
Abstract : Large and productive fisheries occur in regions experiencing or projected to experience ocean acidification. Anchoveta ( Engraulis ringens ) constitute the world's largest single-species fishery and live in one of the ocean's highest p CO2 regions. We investigated the relationship of the distribution and abundance of Anchoveta eggs and larvae to natural gradients in p CO2 in the Peruvian upwelling system. Eggs and larvae, zooplankton, and data on temperature, salinity, chlorophyll a and p CO2 were collected during a cruise off Peru in 2013. p CO2 ranged from 167–1392 µatm and explained variability in egg presence, an index of spawning habitat. Zooplankton abundance explained variability in the abundance of small larvae. Within the main spawning and larva habitats (6–10°S), eggs were found in cool, low-salinity, and both extremely low (less than 200 µatm) and high (more than 900 µatm) p CO2 waters, and larvae were collected in warmer, higher salinity, and moderate (400–600 µatm) p CO2 waters. Our data support the hypothesis that Anchoveta preferentially spawned at high p CO2 and these eggs had lower survival. Enhanced understanding of the influence of p CO2 on Anchoveta spawning and larva mortality, together with p CO2 measurements, may enable predictions of ocean acidification effects on Anchoveta and inform adaptive fisheries management.